Social and Demographic Characteristic of Ulyanovsk Region at the Second Half of 1940-ies: Problem Statement in Domestic Historical Science - O. R. Khasyanov (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
Various theoretical and conceptual approaches allowing to reconstruct demographic processes in the post-war Ulyanovsk region are considered. The author believes that in modern historiography there is no data on the demographic results of the Great Patriotic war, as well as the consequences that were caused by military aggression. It is argued that the dynamics of demographic processes in the post-war Ulyanovsk region was determined not only by direct military consequences, but also by general civilizational trends. It is pointed out, in particular, that the changes in the social space caused by modernization transformed the scale of values of a Soviet man, changed his attitude, worldview, family traditions. It is shown that the demographic transition, which ended in the USSR, was marked not only by an increase in life expectancy, but also by a decrease in the birth rate, which did not fully compensate for the demographic losses of the Soviet people. The author believes that an objective analysis of demographic processes in the post-war Ulyanovsk region is possible only in the framework of an integrated approach, namely, using the theoretical attitudes of supporters and opponents of the theory of “demographic transition.” It is noted that in this historical period the demographic processes depended on the state social policy.